Hydrochemical characteristics of the Oropos coastal aquifers, Attica, Greece - Hermides, Demetrios; Zaxariadis, Dimitrios; Stamatis, George (Bulletin of the Geological Society of Greece, 2020)
This article deals with the hydrochemistry of coastal aquifers of the Oropos plain, Attica, Greece. It is the first study which presents hydrochemical data of the Oropos plain groundwater. Groundwater samples from 34 wells were collected and analyzed for major and heavy metal constituents. Groundwater was differentiated between the Pleistocene confined aquifer and the group of the Holocene, the Miocene and the Mesozoic aquifers based on the electrical conductivity (EC) values and the chlorides content. Groundwater in the Pleistocene sediments presented EC values ranging between 766 and 971μS/cm and chlorides between 95-163mg/l. The group of the rest aquifers presented EC values up to 3770 μS/cm and chlorides up to 993mg/l. The Pleistocene aquifer seems to be protected from seawater intrusion, although, it is located adjacent to the shoreline. In addition, most of the heavy metal concentration exceeded the EU limits. Cd, Fe, Pb, Ni have been determined at 82, 2500, 817, 217 μg/lit respectively. Groundwater was, also, categorized into 2 main water types that of Ca-Mg-HCO3 type indicating recharge of fresh water and that of Ca-Mg-Cl type indicating reverse cation exchange of old Na-Cl waters.